Perlindungan Hukum Terhadap Korban Yang Data Pribadi Passportnya Tersebar Akibat Kelalaian Pemerintah - Galang Surya Mahendra (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
Ensuring the security of people's personal data is the government's responsibility, in accordance with Article 79 paragraph (1) of the Population Administration Law. The sale of government-held documents is one example of how data can be accidentally deleted. If a person's passport information is not adequately secured by the institution responsible for implementing the law, then the person can request compensation as described in Article 2. By using a legal and conceptual approach, this research is included in the category of normative juridical research. As far as legal resources are concerned, there are two main categories: primary and secondary. We use a descriptive normative analysis approach to sort legal information into categories based on the topics discussed. The findings of this research highlight the responsibility of supervisory institutions in ensuring the security of individuals' personal information and the accountability of the state or government in accordance with the Population Administration Law and prevention initiatives. Some possible suggestions to protect people's rights include a more transparent compensation process and clearer regulations prohibiting the sale of personal data.